2019
DOI: 10.1002/jper.19-0129
|View full text |Cite
|
Sign up to set email alerts
|

The role of socioeconomic status and psychosocial factors on gingivitis in socially disadvantaged adolescents

Abstract: Background Evidence on the possible influence of social and psychosocial factors on gingival status in socially disadvantaged children is scarce. The aim of this study is to assess the relationships among socioeconomic status, pattern of dental visits, self‐esteem, oral health beliefs, toothbrushing frequency, oral hygiene effectiveness, and gingivitis in low social status adolescents. Methods A cross‐sectional study was performed involving 406 12‐year‐old students recruited in Manaus, Brazil. Socioeconomic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…On the contrary, previous studies on the relationship between socioeconomic factors and oral health (Sisson 2007; Donaldson et al 2008; Koga et al 2019) suggested the importance of psychological factors, which are related to educational history (Quesnel-Vallée and Taylor 2012; Korhonen et al 2017). Psychological disorders, such as depression and anxiety, are associated with periodontal disease (Genco et al 1999; Park et al 2014; Liu et al 2018).…”
Section: Introductionmentioning
confidence: 83%
“…On the contrary, previous studies on the relationship between socioeconomic factors and oral health (Sisson 2007; Donaldson et al 2008; Koga et al 2019) suggested the importance of psychological factors, which are related to educational history (Quesnel-Vallée and Taylor 2012; Korhonen et al 2017). Psychological disorders, such as depression and anxiety, are associated with periodontal disease (Genco et al 1999; Park et al 2014; Liu et al 2018).…”
Section: Introductionmentioning
confidence: 83%
“…In another words, according to the included and analysed literature, some personal characteristics the same as age [ 18 , 19 ], gender [ 23 ] and race [ 20 , 21 ] can directly and indirectly affect the access to oral and dental health services. These characteristics along with the populations’ physical [ 17 ], dental [ 22 , 25 27 ] and psychological [ 29 31 ] health status can determine the health needs and the health behaviours consequently.…”
Section: Resultsmentioning
confidence: 99%
“…These determinants are more related to the social determinants of health (SDH) and can both influence on the populations’ individual conditions and the organizations’ practices and policies. In another words, the social and cultural factors can highly affect the community’s oral and dental health beliefs [ 22 ], their oral and dental perceived needs [ 33 , 35 ] and the population’ level of education and health literacy [ 36 ]. The economic determinants, similarly can change the community’s oral and dental health behaviours the same as seeking for consultations, treatments or check-up [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…This approach could be managed by dental therapists or nurses under the direction of the dentist, and could include directing patients to online resources or referral for professional help. Whilst there are no adult studies with which to compare these findings, self‐esteem is linked with oral hygiene in adolescents, when oral health beliefs and self‐esteem may indirectly predict gingival bleeding via tooth brushing and oral hygiene effectiveness (Koga et al, 2019).…”
Section: Discussionmentioning
confidence: 99%